Perspectives on the Synoptic Climate Classification and its Role in Interdisciplinary Research. Issue 4 (April 2016) - Dixon, P. Grady; Allen, Michael; Gosling, Simon N.; Hondula, David M.; Ingole, Vijendra; Lucas, Rebekah; Vanos, Jennifer
Abstract: Synoptic climatology has a long history of research where weather data are aggregated and composited to gain a better understanding of atmospheric effects on non‐atmospheric variables. This has resulted in an applied scientific discipline that yields methods and tools designed for applications across disciplinary boundaries. The spatial synoptic classification (SSC) is an example of such a tool that helps researchers bridge methodological gaps between disciplines, especially those studying weather effects on human health. The SSC has been applied in several multi‐discipline projects, and it appears that there is ample opportunity for growth into new topical areas. Likewise, there is opportunity for the SSC network to be expanded across the globe, especially into mid‐latitude locations in the Southern Hemisphere. There is some question of the utility of the SSC in tropical locations, but such decisions must be based on the actual weather data from individual locations. Despite all of the strengths and potential uses of the SSC, there are some research problems, some locations, and some datasets for which it is not suitable. Nevertheless, the success of the SSC as a cross‐disciplinary method is noteworthy because it has become a catalyst for collaboration.